THE PRINCIPLE OF AUTONOMY OF STATE ADMINISTRATION AUTHORITIES IN THE REPUBLIC OF SERBIA - Stevandić, Danilo (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The principle of autonomy constitutes a legally regulated relationship between administrative authorities and other state bodies or non-state entities. It entails relative—objectively determined by law—organizational and functional autonomy of administrative authorities, as well as the functional autonomy of authorized officials. Following a lexical-semantic analysis of the term and the delineation of related concepts, the paper first presents a theoretical and legal framework of the autonomy of administrative authorities, followed by a historical and legal overview and an analysis of the normative framework in the Republic of Serbia. The author concludes that constitutional and statutory provisions provide a solid normative basis for the autonomy of administrative authorities, yet there remains a need for its further enhancement. More importantly, there is a constant need to improve political practice and legal tradition in the consistent application of legal norms, that is, to develop a firmly established understanding and general consensus regarding the inadmissibility of undue influence on the work of administrative authorities.
Keywords: principle of autonomy; principle of separation of powers; principle of accountability; principle of legality; administrative authorities; undue influence